Morphological and genetic variation of local loach (Nemacheilus spp.) from Lumajang, East Java, Indonesia - DWI ANGGOROWATI RAHAYU; WIDOWATI BUDIJASTUTI; SUNU KUNTJORO; WINARSIH WINARSIH; ENDIK DENI NUGROHO; RENI AMBARWATI; ULFI FAIZAH; CAHYA AJENG VALENTA TRESNA SULUNG; RUSDIANTO RUSDIANTO; NOORHIDAYAH BINTI MAMAT (Society for Indonesian Biodiversity, 2025)
Abstract. Rahayu DA, Budijastuti W, Kuntjoro S, Winarsih, Nugroho ED, Ambarwati R, Faizah U, Sulung CAVT, Rusdianto R, Mamat NB. 2025. Morphological and genetic variation of local loach (Nemacheilus spp.) from Lumajang, East Java, Indonesia. Biodiversitas 26: 2896-2907. The genus Nemacheilus is a part of the family Nemacheilidae within the order Cypriniformes, comprising several morphologically similar fish species found in East Java, Indonesia. However, species identification in Lumajang remains unavailable. This study aimed to analyze morphological and genetic diversity of local loach species from Lumajang, East Java, contributing to the existing knowledge with new records. The experiment was carried out through diagnostic identification, meristic, and morphometric analyses, using Past.403 software for correlation assessments. Pectoral fin samples were preserved in high-purity ethanol for DNA extraction, followed by Polymerase Chain Reaction (PCR) targeting mitochondrial genomes, Recombinase-Activating Gene proteins 1 (RAG1), and mitochondrial Cytochrome C Oxidase I (COI) to explore phylogenetic relationships among Nemacheilidae species through maximum likelihood methods. Morphological identification showed two local loaches, Nemacheilus chrysolaimos (Valenciennes, 1846) and Nemacheilus fasciatus (Valenciennes, 1846) with two variants (dominant black color and yellow color). Several morphometric parameters showed high correlations, such as TL with SL, HL with Snout Length (SnL), and Dorsal Fin Length (DFL) with Anal Fin Length (AFL). The COI locus showed high genetic variation with 126 variable sites across 489 base pairs. Meanwhile, the RAG1 gene had a lower variation with 33 variable sites across 681 base pairs, with phylogenetic analysis showing two distinct clades. This comprehensive study enhanced the understanding of morphological and genetic variation in Nemacheilus species, related to conservation efforts and sustainable aquaculture.